A clinico-microbiologic study comparing the efficacy of locally delivered chlorhexidine chip and diode LASER as an adjunct to non-surgical periodontal therapy - Bansal, Vrishti (J Oral Biol Craniofac Res, 2019)
BACKGROUND: Considering the microbial etiology of the periodontal disease, the periodontal therapy aims to control or abolish the pathogenic microbes. The gold standard scaling and root planing procedure has been used since time immemorial but the drawbacks associated with it have led to the development of various adjunctive means. The current study was therefore, performed to comparatively assess the efficacy of local delivery of chlorhexidine and 808-nm diode LASER as an appurtenance to scaling and root planing in patients with chronic periodontitis. METHODS: In a randomized split mouth evaluation, 30 patients having probing depth of ≥5 mm which bled on probing at least at 3 different sites were included. At baseline, the evaluation of plaque index, bleeding index, probing pocket depth and clinical attachment level was done and the microbial samples were collected for the assessment of spirochetes, motile rods and coccoid cells. The 3 selected sites of each subject were allocated to 3 different groups A, B, C viz; Scaling and root planing (SRP) + chlorhexidine chip, SRP + diode LASER and SRP respectively. The patients were recalled after 4 weeks to re-evaluate the clinical and microbiological parameters. RESULTS: All the parameters significantly reduced from baseline to 4 weeks in all the 3 groups. Intergroup comparisons revealed remarkable difference between group A and C and group B and C, respectively; no notably significant difference was found between group A and B. CONCLUSION: The additional use of LASER and chlorhexidine chip assures anti-inflammatory effect and anti-microbial effect that allows reduction in bacterial counts and promotes healing. The use of adjuncts have been found to be efficacious in controlling disease and promoting periodontal health and thereby reducing the need for surgical procedures to be undertaken.